Analisis Pengaruh Beban Tugas Akademik Dan Digital Fatigue Terhadap Prestasi Akademik Siswa: Analysis of the Influence of Academic Task Load and Digital Fatigue on Students' Academic Achievement - Bernadin Maria Noenoek Februati; Evi Gusliana; Hadi Prayitno; Muhammad Ridhwan; Mozart Malik Ibrahim (ITScience (Information Technology and Science), 2024)
Students may experience digital fatigue as a result of substantial increases in academic workload and heavy reliance on digital technologies for learning. This study aims to analyze the effects of academic workload and digital fatigue on students’ academic achievement. A quantitative approach using survey techniques was used for this study, involving 200 students from the secondary school level. A questionnaire was used to collect data, which was then analyzed using multiple linear regression. The results showed a negative relationship between students’ academic achievement and workload, indicating that students’ academic achievement decreased in relation to the number of tasks they were asked to complete; this means that the more academic tasks students had to complete, the lower their academic achievement. The main factor that plays a role in this relationship is digital fatigue, which arises from the excessive use of digital devices in the learning process. Digital fatigue results in mental and physical fatigue, thus exacerbating the impact of academic pressure on students’ achievement. Digital fatigue occurs when students are exposed to digital device screens for too long without sufficient breaks. Common symptoms include eye fatigue, difficulty concentrating, sleep disturbances, and increased levels of stress and anxiety. In the long term, this condition can lead to decreased motivation to learn and negatively impact students’ emotional and psychological well-being. Effective strategies to reduce digital fatigue, such as better time management, variety in learning methods, and adequate breaks in academic activities, are needed, and it is important to provide students with balanced academic tasks so that they are not overburdened. Implementing these steps will help students focus on their studies without negatively impacting their emotional or psychological well-being.